2021
DOI: 10.1039/d0na00935k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface charge of graphene quantum dots on their uptake and clearance in melanoma cells

Abstract: Graphene quantum dots (GQDs) continue to draw interest in biomedical applications. However, their efficacy gets compromised due to their rapid clearance from body. On one side, rapid clearance is desired...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
(71 reference statements)
2
17
0
Order By: Relevance
“…The Raman spectra of GQDs and MA‐GQDs are shown in Figure 9. The GQD spectrum reveals the presence of the characteristic D and G bands at 1365 cm −1 and 1597 cm −1 respectively, comparable to what has been previously reported, [ 30 ] while the spectrum of MA‐GQDs shows the D and G bands at 1428 cm −1 and 1597 cm −1 respectively. The Raman spectrum of MA‐GQDs indicated a red‐shift of the D band and decrease in intensity of G band, which may be a result of the changes in the surface chemistry of the materials affecting the interaction of the photons.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The Raman spectra of GQDs and MA‐GQDs are shown in Figure 9. The GQD spectrum reveals the presence of the characteristic D and G bands at 1365 cm −1 and 1597 cm −1 respectively, comparable to what has been previously reported, [ 30 ] while the spectrum of MA‐GQDs shows the D and G bands at 1428 cm −1 and 1597 cm −1 respectively. The Raman spectrum of MA‐GQDs indicated a red‐shift of the D band and decrease in intensity of G band, which may be a result of the changes in the surface chemistry of the materials affecting the interaction of the photons.…”
Section: Resultssupporting
confidence: 88%
“…The GQD spectrum reveals the presence of the characteristic D and G bands at 1365 cm À1 and 1597 cm À1 respectively, comparable to what has been previously reported, [30] while the spectrum of MA-GQDs…”
Section: Raman Spectra Of Gqds and Ma-gqdssupporting
confidence: 87%
“…FTIR and Raman spectroscopy were conducted to further characterize the nanocomposite films. FTIR analysis of neat LS revealed characteristic peaks at 3375, 1568, 1410, 1000–1100, and 618 cm –1 corresponding to an −OH stretching peak from phenolic and carboxylic acids, −CC– stretching, −SO stretching, −C–O stretching band from primary, secondary alcohols and aliphatic ether of LS, and −C–H vibration, respectively (Figure f). , In the case of the P­( n BA- stat -BzMA)/rGO film, characteristic peaks for the −CO stretching band, −C–H bending band from the methyl group, −C–O stretching vibration, and a strong −C–H band originating from a substituted benzene derivative (BzMA) were observed at 1724, 1455, 1000–1100, and 680–760 cm –1 , respectively (Figure f). We observed the presence of peaks from both P­( n BA- stat -BzMA)/rGO and LS in the P­( n BA- stat -BzMA)/rGO/LS films as expected. For example, the presence of peaks, such as 1728, 1455, and ∼700–760 cm –1 , was a contribution from P­( n BA- stat -BzMA)/rGO, whereas peaks at 3375, 1571, 1396, 1000–1100, and 617 cm –1 can be assigned to the contribution from LS (Figure f).…”
Section: Resultsmentioning
confidence: 99%
“…FTIR analysis of neat LS revealed characteristic peaks at 3375, 1568, 1410, 1000−1100, and 618 cm −1 corresponding to an −OH stretching peak from phenolic and carboxylic acids, −CC− stretching, −SO stretching, −C−O stretching band from primary, secondary alcohols and aliphatic ether of LS, and −C−H vibration, respectively (Figure 3f). 40,41 In the case of the P(nBA-stat-BzMA)/rGO film, characteristic peaks for the −CO stretching band, −C−H bending band from the methyl group, −C−O stretching vibration, and a strong −C−H band originating from a substituted benzene derivative (BzMA) were observed at 1724, 1455, 1000−1100, and 680− 760 cm −1 , respectively (Figure 3f). 42−44 We observed the presence of peaks from both P(nBA-stat-BzMA)/rGO and LS in the P(nBA-stat-BzMA)/rGO/LS films as expected.…”
Section: Resultsmentioning
confidence: 99%
“…Optical [138], electrical [139], and biological [140,141] properties of GQDs are intrinsically dependent on their size. For instance, Deng and coauthors demonstrated the influence of size over the electrocatalytic activity of graphene exfoliated via ball milling.…”
Section: Effect Of the Size Of Gqds In Their Electrochemical Performancementioning
confidence: 99%